Penerapan Tiga Akses Teknologi Informasi Sebagai Upaya Peningkatan Sumber Daya Dalam Pembangunan Kampung Inspirasi - Devi Aryaning Tyas; Winda Budi Lestari; Bayu Cahya Khurnia Yudha; Henri Bambang Suratno; Iqbal Ikhlasul Amal; Ardyas Setya Nugraha; Muhammad Hasan; I Gede Wiryawan (PRIMA: Journal of Community Empowering and Services, 2023)
Implementation of Three Information Technology Access Points as an Effort to Enhance Resources in the Development of Kampung Inspirasi. Sumbersalak village, Ledokombo District, Jember Regency is located at the foot of Mount Raung, with the geographical conditions of many coffee plantations. The majority of the people there work as coffee farmers and breeders of goats or cattle. There is the Sekar Wangi farmer group, a collection of several potential residents with visionary souls. The activities carried out by the farmer groups range from making Arabica and Robusta coffee. All community activities are carried out at Rumah Inspiration. The place is for various activities, including children's learning activities, making compost, and even the Sekar Wangi farmer group center. One of the informants we interviewed was the head of the farmer group in Sumbersalak Village. From the survey, the majority of people work as coffee farmers, and many piles of coffee skin waste and livestock manure are left unattended so that they can pollute the environment. Residents usually sell the coffee skin itself for 300 rupiahs per kilogram. Therefore, a design was made regarding the manufacture of compost from coffee husk waste and livestock manure using a compost mixer with digital technology. It aims to utilize waste which can later be utilized as a result in organic compost by coffee farmers and traded online through e-commerce so that more people know about this product, it can improve the economy of the Sumbersalak villagers later.